Prolonged mask wearing changed nasal microbial characterization of young adults during the COVID-19 pandemic in Shanghai, China - Xiang, Guoxiu; Xu, Kai; Jian, Ying; He, Lei; Shen, Zhen; Li, Min; Liu, Qian (Frontiers in Immunology, 2023)
Face masks have become a common sight during Corona Virus Disease 2019 pandemic in many countries. However, the impact of prolonged face masks wearing on nasal microbiota of healthy people is not fully understood.In this study, we compared the nasal microbiota of 82 young adults who wore face masks for an extended period of time to 172 mask-free peers from same school recruited before COVID-19 pandemic via 16S ribosomal RNA gene sequencing. Diversity, composition and function of nasal microbiota between the two groups were analyzed.Prevalence of commensal bacteria colonized in the nasal cavity was determined by culture-based analysis.We observed that prolonged face mask wearers had significantly different nasal microbial characterization and metabolic function compared to mask-free controls from 2018. Specifically, the nasal microbiota of the prolonged mask wearers displayed increased abundance of Staphylococcus, Pseudoalteromonas, Corynebacterium, etc.Meanwhile, the abundance of several genera including Bacteroides, Faecalibacterium and Agathobacter, etc. was decreased. Besides, we observed that COVID-19 infection history did not affect the composition of nasal microbiota significantly. Additionally, the culture-based analysis revealed Staphylococcus aureus and Corynebacterium accolens increased, and Staphylococcus epidermidis decreased in the nasal cavity of prolonged mask wearers.Overall, our study suggests that prolonged face mask wearing can significantly alter the nasal microbiota.